Hermeneutika sebagai Metode Tafsir: Mengurai Konstruksi Pengetahuan Generasi Z Kota Malang - M. Miski; Lulu Fauziah Priyandini; M. Rozik Sudawam; Megawati Ayu Rahmawati Wardah; Alvian Chandra Alim (Khazanah Theologia, 2021)
This study is intended to answer three main questions. First, how does the Z generation in Malang City responds to the use of hermeneutics as a method of interpreting the Qur'an by Muslim scholars? Second, how is the process of transmitting their knowledge about it? And third, how is the construction of their knowledge about the ideal interpretation of the Qur'an and can respond to socio-religious dynamics and phenomena? This study is a field study, while the primary respondents are Z generation in Malang City. The use of descriptive, hermeneutic, and intertext analysis models on data, the results of this study showed that there are differences conveyed by the Z generation of Malang City related to the use of hermeneutics as a method of interpretation of the Qur'an: some of them accept it, while others reject it. The transmission of their knowledge about hermeneutics also varies; most of them are correlated with social media, some are still conventional, which relies on information from teachers, and so on. This showed that generation Z of Malang city is not entirely averse to issues that tend to be controversial. Moreover, the authority for interpreting the Qur'an has not entirely shifted from the real world to cyberspace, no matter how dependent they are on the new media.